Rapid detection of spermine by using a cost-effective carbon nanostructured aptasensor - Howyn Tang; Hossein Pouri; Chao Lu; Jin Zhang (Nano TransMed)
Spermine is a polyamine that participates in ion channel regulation and cell proliferation. It is considered a biomarker for pancreatic cancer. In this study, a carbon nanostructure-based aptasensor has been developed to rapidly detect spermine in solution by relying on Förster resonance energy transfer (FRET). The FRET donor, carbon quantum dots (CDs), are bioconjugated to aptamers specific for spermine. CDs have an average diameter of 5.0 ± 2.5 nm and have the maximum fluorescence intensity emitting at 510 nm when excited at 400 nm. Due to the π-π* interaction between DNA-based aptamer and GO, a FRET quencher, CDs bioconjugated with aptamer (CDs-aptamer) can directly attach on the surface of GO, resulting in significant FRET quenching. In the presence of spermine, GO and CDs-Aptamer separate, and the fluorescence intensity of CDs is restored. The restored fluorescence intensity of CD-aptamer can be observed when the concentration of spermine increases from 0.1 to 250 nM. The sensing system in this study could be a cost-effective, user-friendly method to quickly detect spermine, a biomarker for pancreatic cancer.